Disinfection of Archived Material by Radiation Processing Technology Keeping the Material Integrity - Pramanik, Md Kamruzzaman; Miah, Abdul Bathen; Alam, Md Khorshed (Bangladesh Journal of Microbiology, 2018)
The aim of the study was to preserve paper-based archived material for a long period of time using ionizing radiation/nuclear technique. To conduct this research, old note-pad samples were selected as tentative archived material. Samples were prepared and irradiated at a series of radiation doses e.g. 0, 2.0, 4.0, 6.0, 8.0, 10.0 and 14.0 kGy at a dose rate of 12.8 kGy/h from panaromic Batch type 80 kCi 60Co source. After irradiation, different quality parameters such as microbiological (Total Viable Bacterial Count, Total Fungal Count), mechanical (Tensile Strength, Percent of Elongation at Break and Elastic Modulus) and color properties (L-value, a-value and b-value) of the samples were assessed to observe the immediate effect of ionizing radiation on these properties. Results showed that the total bacterial count of unirradiated (control) paper were 4.0X102 cfu/g and radiation dose of 2.0 kGy was enough to eliminate the microbial load completely. Among mechanical properties, tensile strength (TS) of unirradiated sample was 16.23 MPa and it was gradually increased as the dose increased and finally reached upto 18.99 MPa at a dose of 14 kGy causing the TS-change above significant level (p < 0.05). Though changes of percent of elongation at break (EB) due to irradiation was insignificant, elastic module (EM) increased as the radiation dose increased gradually. EM of non irradiated sample was 381.85N/m2 and it started changing significantly from 6.0 kGy and finally reaches upto 477.03 N/m2 at 14.0 kGy. Results showed that L-value of colour parameter changed very slightly though a and b-value changed significantly from 6.0 kGy. From these findings it can be inferred that a radiation dose of 4.0 kGy might be used to conserve the cultural heritage including valuable paper-based archived materials. Bangladesh J Microbiol, Volume 33, Number 1-2, June-Dec 2016, pp 1-4